PENINGKATAN INOVASI WISATA DESA WATUAJI MELALUI PENERAPAN WEBSITE DAN LAYANAN OUTBOND - Riyoko, Sisno; Azizah, Noor; Ariyanto, Shodiq Eko; Saputro, Yayan Adi; Laila, Azzah Nor (Universitas Mataram, 2024)
Watuaji Village has several tourism pioneers, but they are not yet organized, have no visitors, and are not yet known by outsiders. The priority problem in Watuaji village is the management and marketing aspects of tourism. So the service team partnered with BUMDes Sae and GAPOKTAN Sidodadi Makmur Watuaji to overcome these problems. The goals of this community service program is to improve partner empowerment in the aspects of knowledge and skills related to management, and improve partner skills in making Watuaji tourism promotion. This community service program uses some methods, they are discussion method at the preparation stage with coordination and socialization. The training stage with tutorial methods, lectures, discussions, and practice. The mentoring stage with practice and project methods. Evaluation stage with questionnaire, test and discussion methods. The results of this community service program are improving the management aspect, partners have increased knowledge with an average post-test score of 80. Partner empowerment, 80% increased their skills in managing and innovating tourism services. Tourism is managed together, and there is an innovative outbound package service. In the marketing aspect, there was an increase in partner knowledge at an average of 80. Partner empowerment in the marketing aspect, 80% of partners increased their skills in conducting online marketing through the website. The result is an increase in the number of tourist services, marketing media, and the number of tourist visitors in Watuaji Keling Jepara village.